Cognitive Control Deficits in Children With Subthreshold Attention-Deficit/Hyperactivity Disorder - Chen, Caiqi; Li, Zhuangyang; Liu, Xiqin; Pan, Yongling; Wu, Tingting (Frontiers in Human Neuroscience, 2022)
Subthreshold Attention-Deficit/Hyperactivity Disorder (ADHD) is defined as a neurobiological condition with some core inattentive or hyperactive/impulsive symptoms of ADHD which do not meet the full diagnosis clinically. Although it has been well documented that deficits in cognitive control, a high-level cognitive construct closely related to attention, are frequently found among children with ADHD, whether subthreshold ADHD is also associated with similar deficits remains unclear. In this study, we examined the attention functions and the cognitive control capacity (CCC) in children with ADHD (n = 39), those with subclinical ADHD (n = 34), and typically developing peers (TD, n = 36). The results showed that the ADHD and subthreshold ADHD groups exhibited similar patterns of the impaired executive function of attention (revealed as an augment in flanker conflict effect) and reduced cognitive control capacity, and no significant difference was found between the two groups. It suggests that although children with subthreshold ADHD have not met the full criteria of ADHD, they showed reduced efficiency in cognitive control and attention function, similar to children with ADHD.